2011
DOI: 10.1121/1.3589255
|View full text |Cite
|
Sign up to set email alerts
|

Comparing spatial tuning curves, spectral ripple resolution, and speech perception in cochlear implant users

Abstract: Spectral ripple discrimination thresholds were measured in 15 cochlear-implant users with broadband (350-5600 Hz) and octave-band noise stimuli. The results were compared with spatial tuning curve (STC) bandwidths previously obtained from the same subjects. Spatial tuning curve bandwidths did not correlate significantly with broadband spectral ripple discrimination thresholds but did correlate significantly with ripple discrimination thresholds when the rippled noise was confined to an octave-wide passband, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 26 publications
3
121
1
Order By: Relevance
“…Another measure of spectral resolution uses broadband spectral ripple discrimination, where listeners have to discriminate between a spectral ripple pattern and its inverse-phase counterpart. With this method, Anderson et al (2011) showed that, on average, CI listeners could discriminate phase-inverted spectral ripples up to 1.68 ripple/ octave. The detection of the 3.6-semitone shift in our experiment would require discrimination of 1.67 ripple/octave, so average CI listeners could perhaps just detect this VTL shift.…”
Section: Gender Categorization By CI Listenersmentioning
confidence: 99%
“…Another measure of spectral resolution uses broadband spectral ripple discrimination, where listeners have to discriminate between a spectral ripple pattern and its inverse-phase counterpart. With this method, Anderson et al (2011) showed that, on average, CI listeners could discriminate phase-inverted spectral ripples up to 1.68 ripple/ octave. The detection of the 3.6-semitone shift in our experiment would require discrimination of 1.67 ripple/octave, so average CI listeners could perhaps just detect this VTL shift.…”
Section: Gender Categorization By CI Listenersmentioning
confidence: 99%
“…One psychophysical task that is believed to measure spectral resolution is spectral ripple discrimination (Supin et al, 1994;Henry et al, 2005;Won et al, 2007;Anderson et al, 2011). For this procedure, the listener is required to discriminate between a spectrally rippled noise stimulus (i.e., broadband noise containing regular variations in amplitude along the frequency axis) and another stimulus in which the positions of spectral peaks and valleys are reversed.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the spectral modulation depth is held constant and the ripple rate is adaptively varied to find the listener's ripple discrimination threshold. Spectral ripple discrimination has been shown to correlate with other measures of spectral resolution in cochlear-implant (CI) users, such as spatial tuning curves (Anderson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations